ADVANCEMENTS IN MARBURG VIRUS VACCINE DEVELOPMENT: UNRAVELLING RECENT FINDINGS. A NARRATIVE REVIEW. - Amna Zaheer; Daniyah Zehra Hussain; Ahmad Akhtar (Student’s Journal of Health Research Africa, 2024)
Marburg Virus Disease (MVD) is a lethal single-stranded RNA virus transmitted by Egyptian rousette bats, causing 12 surges in Sub-Saharan Africa, including a recent outbreak in Tanzania in 2023. With a fatality rate of approximately 90%, no approved vaccines currently exist. Ongoing research explores potential candidates, such as a recombinant vesicular stomatitis virus (VSV)-based vaccine and MVA-BN-Filo, aiming to combat this deadly infection. The objective of this review is to comprehensively examine Marburg virus vaccines, exploring various candidates and their development stages, efficacy in non-human primates and human studies, and challenges faced in the development process. Various vaccines are under development, including Ad26, Ad5, viral vector, and DNA vaccines. Promising candidates like Ad26.Filo and ChAd3-MARV have emerged. Additionally, VLP-based, DNA plasmid and rVSV-based vaccines are discussed, highlighting their effectiveness and challenges in development, such as limited information, gene expression issues, and outbreak control measures. The implications for future research and clinical practice/policy development are significant. Marburg virus vaccine development shows promise in mitigating the threat posed by this deadly pathogen. Despite complex challenges, advancements in vaccine candidates offer hope. Continued research and development may lead to the successful prevention of major Marburg virus outbreaks. Ongoing clinical trials indicate potential breakthroughs in a short period, contributing to public health protection.